Global Futures in East Asia : Youth, Nation, and the New Economy in Uncertain Times - Anagnost, Ann; Arai, Andrea, 1956-; Ren, Hai, 1965- (Contemporary issues in Asia and the Pacific., 2012)
"The East Asian economic miracle of the twentieth century is now a fond memory. What does it mean to be living in post-miracle times? For the youth of China, Taiwan, Japan, and South Korea, the opportunities and challenges of the neoliberal age, deeply shaped by global forces in labor markets, powerfully frame their life prospects in ways that are barely recognizable to their parents. Global Futures in East Asia gathers together ethnographic explorations of what its contributors call projects of "life-making." Here we see youth striving to understand themselves, their place in society, and their career opportunities in the nation, region, and world. While some express optimism, it is clear that many others dread their prospects in the competitive global system in which the failure to thrive is isolating, humiliating, and possibly even fatal."--Publisher's website.